(untitled) (American Journal of Business Management, Economics and Banking, 2026)
Nigeria is amongst few countries that are endowed with natural resources like crude oil and liquified natural gas. Both resources have brought about high level of oil and gas industrial activities in the country, which have led to huge increase in tax revenue (PPT inclusive). But the poor conditions of public utilities in Nigeria has led to so many questions about the usefulness of taxation in Nigeria. This study therefore investigated the impact of Petroleum Profit Tax on the economic growth of Nigeria, from 2011 – 2023. Petroleum Profit Tax revenues were employed as the independent variable, while Gross Domestic Product (GDP) which was used as a proxy for economic growth served as the dependent variable. Data were sourced from the Central Bank of Nigeria (CBN) statistical bulletin and Federal Inland Revenue Service (FIRS) tax and statistics report. The data were analyzed using the regression analysis. The result showed that Petroleum Profit Tax has positive but non-significant effect on Gross Domestic Product (GDP). The study recommended that government should diversify Nigeria’s revenue base by strengthening other sectors of the economy in order to reduce dependency on Petroleum Profit Tax, thereby mitigating the risks associated with fluctuating oil prices. The study also recommended that the government should use reasonable portion of funds generated through Petroleum Profit Tax to provide social amenities for the benefit of the citizens.